DIGITALLY DESIGNED AND MANUFACTURED LASER DOPPLER PROBE HOLDER FOR TOOTH VITALITY ASSESMENT - A PRELIMINARY STUDY FOR A NOVEL TECHNIQUE - Ciora Edmond; Miron Mariana; Todea Carmen; Jivănescu Anca (Romanian Society of Oral Rehabilitation, 2022)
Aim of the study. The purpose of this study was to develop a new method to facilitate laser Doppler tooth vitality assessment, using a digitally designed probe holder. Material and methods. A laser Doppler probe holder was digitally designed after scanning a casted model and then the probe holder was 3D printed. In order to test the probe holders, a straight optical probe from MoorLab instruments was used. Conclusions. The probe holder proved to be stable and could be used to obtain accurate signal acquisition in these experimental conditions, however further testing is necessary.